2011
DOI: 10.1038/oby.2010.132
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of QT Shortening by Weight Loss and Physical Training in Obese Subjects With Coronary Heart Disease

Abstract: This study aims to describe the changes that a period of low‐calorie diet and physical training determines in heart rate and in corrected QT (QTc) interval in obese patients with coronary heart disease (CHD) and to verify whether it is effective in shortening the QT interval using three different methods for QT correction. Two hundred and seventy obese white patients (162 males—60%) affected with stable CHD and treated with β‐blockers were retrospectively studied in the setting of a program aimed at losing wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These authors also observed that rate-corrected QT (QTc) was not changed by pregnancy and so concluded that the duration of ventricular repolarisation is entirely rate-dependent. Gondoni et al (2011) found a strong relationship between ejection fraction and QTc and since it is well documented that ejection fraction is unaltered with pregnancy (Capeless & Clapp, 1989), this may explain the unaltered QTc with gestation. We have extended these observations by showing that uncorrected QTe and QTa are significantly reduced even by the end of the first trimester and notably in all physiological states.…”
Section: Discussionmentioning
confidence: 71%
“…These authors also observed that rate-corrected QT (QTc) was not changed by pregnancy and so concluded that the duration of ventricular repolarisation is entirely rate-dependent. Gondoni et al (2011) found a strong relationship between ejection fraction and QTc and since it is well documented that ejection fraction is unaltered with pregnancy (Capeless & Clapp, 1989), this may explain the unaltered QTc with gestation. We have extended these observations by showing that uncorrected QTe and QTa are significantly reduced even by the end of the first trimester and notably in all physiological states.…”
Section: Discussionmentioning
confidence: 71%
“…Many studies that followed showed that obesity can cause prolonged QTc interval [9][10][11]. Much of comorbidities associated with obesity can be improved or prevented with body weight (BW) reduction [12]. Effects of changes in body mass index (BMI) on cardiovascular risk are verified in the Framingham study.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies observed the effects of weight reduction on the QTc interval in obese patients, but the results are conflicting. The most of the studies observed that QTc interval is shortening during the weight reduction [14][15][16][17], but some studies haven't shown significant changes in the QTc interval during weight reduction [12,18]. It is surely important to monitor the QTc interval during the treatment of obesity in order to prevent adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Bazett equation is known to be most sensitive to biasing effects of HR which appear to be particular important in the context of weight loss since weight loss is often accompanied by a reduction in HR. It should be noted, however, that the extent of weight loss induced by a hypocaloric diet and exercise in the abovementioned negative study [9] was only moderate, i.e. a BMI reduction of −1.2 kg m −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, weight loss, in particular when induced by bariatric surgery, has been found to reduce QT interval (QTc) length in many studies (for overview see Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the validity of this observation has been challenged by one previous study [9] that demonstrated that the significance of QTc shortening upon weight loss gets lost when the QT interval is corrected for heart rate (HR) by using Fridericia or Framingham correction equation instead of the most commonly used Bazett equation. Indeed, the Bazett equation is known to be most sensitive to biasing effects of HR which appear to be particular important in the context of weight loss since weight loss is often accompanied by a reduction in HR.…”
Section: Introductionmentioning
confidence: 99%